Hierarchical Elements, Local Mappings and the $H$-$P$ Version of the Finite Element Method (Ⅱ) (Journal of Computational Mathematics, 1988)
This is the second half of the article. The rate of convergence for the $h$-$p$ version with geometric meshes is discussed.